Social Circumstances of Deviant People, Case Study in Gjakova Region - Avdiaj, Bekim (European Journal of Multidisciplinary Studies, 2016)
One of the factors influencing groups to hold together as one united ‘body’ for a social stability, is also the level of appearance of criminality within the region. Alongside evolution of the society, crime has also evolved and refined. Therefore, in the modern world of technology and science, criminality emerges in most diverse and most advanced forms. Based on that, criminality is encountered in every pore of society, irrespective of development, tradition, culture and nationality, and that from the local level, regional, state and all the way to international dimensions. This is furthermore sustained particularly by social evolutions experienced by the countries in transition, which were subject of a ‘reformation’ in all social spheres thus without sparing the human values. These trends of global development have, through some deviant cases, resulted with situations where all the existing social norms are being relinquished. Regardless of where you may happen to be, whatever newspaper you read, whatever news edition you watch on TV, one cannot but note that various criminal offences are being discussed or reported about, starting from the most common ones all the way to the terrorist acts. Based on the number and type of criminality, and based on the number of deviant persons, from 1999 onwards Gjakova region results with entirely new ‘behaviour’ in this direction. Therefore, current studying and analysing of social circumstances related deviant persons of this region consists of an immense and specific importance. Social circumstances and other factors of such persons shall be reflected through this study and that from the analysis generated from 95 of them which, in relation to the number of criminal offences reported with the law enforcement authorities from 2001 until 2012, appears to be 0. 41 percent. The sample included convicted deviant persons coming from the population of Gjakova region.
Keywords: social, criminality, social development and Gjakova region